1980
DOI: 10.5636/jgg.32.129
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric E-region drifts at Yamagawa during IQSY.

Abstract: IonosphericE -region drifts at Yamagawa are studied from the published results for the year 1964. The drift pattern is highly seasonally dependent and similar to that reported for tropical latitude stations of Ahmedabad and Udaipur. Small changes due to lunar effects have been noted to occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…But it was the ionospheric drift data at Thumba, which showed that the drift speed during the midday hours in the E and F regions of the ionosphere decreased progressively with increasing Kp index (Rastogi et al, 1971b). Patel and Chandra (1982) showed that with the increasing Kp index, the drift speed at stations within the Sq focus latitude and the equator, Thumba, Tiruchirapalli and Ahmedabad decreased steadily. However at station north of the Sq focus latitude, Yamagawa and Sibzimir, the daytime drift speed (eastward) increased steadily with the increase of Kp index.…”
Section: Equatorial Ionospheric Driftsmentioning
confidence: 99%
“…But it was the ionospheric drift data at Thumba, which showed that the drift speed during the midday hours in the E and F regions of the ionosphere decreased progressively with increasing Kp index (Rastogi et al, 1971b). Patel and Chandra (1982) showed that with the increasing Kp index, the drift speed at stations within the Sq focus latitude and the equator, Thumba, Tiruchirapalli and Ahmedabad decreased steadily. However at station north of the Sq focus latitude, Yamagawa and Sibzimir, the daytime drift speed (eastward) increased steadily with the increase of Kp index.…”
Section: Equatorial Ionospheric Driftsmentioning
confidence: 99%
“…The results reported from low altitude and equatorial belt region suggested that drift speed decreases with magnetic activity index.Kelleher 9 , noticed an increase in the Es drift at Slough (51. 12 , studied the effect of magnetic activity on drift speed at various stations and found a negative correlation between drift speed and magnetic activity index in both E and F regions at all stations located between equator and 35 o N geog.latitude. They have also reported that a positive correlation at high latitudes beyond Sq.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Briggs and Spencer, 1954;Patel and Chandra, 1982), equatorial latitudes (Skinner et al, 1963;Rastogi et al, 1972;Vyas and Chandra 1979), and low latitudes (Rastogi et al, 1978;Patel and Chandra 1980;Vyas 1989). These studies have given rise to a fair understanding of various morphological features, including seasonal variations of the horizontal ionospheric drifts.…”
Section: Introductionmentioning
confidence: 99%